Corrigendum to ＂The Properties of a New Subclass of Harmonic Univalent Mappings - Liu, Zhi-Hong; Li, Ying-Chun (Abstract and Applied Analysis, 2015)
In the paper entitled “The Properties of a New Subclass of Harmonic Univalent Mappings” [1], the presentation of Lemma 9 and Theorem 10 (in Section 3) is taken from that of Lemma 3.1 and Theorem 3.2 of Muir paper’s “S. Muir, “Harmonic mappings convex in one or every direction,” Computational Methods and Function Theory, vol. 12, no. 1, pp. 221–239, 2012”.